2012
DOI: 10.2174/1875399x01205010100
|View full text |Cite
|
Sign up to set email alerts
|

The Nonlinear Nature of Learning - A Differential Learning Approach

Abstract: Traditional learning approaches are typically based on a linear understanding of causality where the same cause leads to the same effect. In recent years there has been increasing interest in the complexity of nature and living phenomena, with significant insights provided by models of change that are based on a nonlinear understanding of causality, where small causes can lead to big effects and vice versa. In this vein, learning processes seem to be more successful for inducing behavioral change when teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 14 publications
5
111
2
8
Order By: Relevance
“…This result corresponds to classical memory effects that follow learning procedures mainly characterized by performance repetitions (Schöllhorn, Hegen, & Davids, 2012) and the hysteresis phenomena (Frank et al, 2008). Traditional practice through repetition, with short periods without practice between sessions, generates more consistent motor patterns in the short-term memory that fade after long periods without practicing.…”
Section: Discussionsupporting
confidence: 64%
“…This result corresponds to classical memory effects that follow learning procedures mainly characterized by performance repetitions (Schöllhorn, Hegen, & Davids, 2012) and the hysteresis phenomena (Frank et al, 2008). Traditional practice through repetition, with short periods without practice between sessions, generates more consistent motor patterns in the short-term memory that fade after long periods without practicing.…”
Section: Discussionsupporting
confidence: 64%
“…This traditional approach is characterised by a conventional practice sequence which starts with the introduction of technical skill(s), followed by students' repetitive attempts to reproduce teacher-prescribed movement 'templates' in isolated drills, finishing with a game (Hopper et al 2009). This decontextualised approach to practice is not compatible with the aim of developing intelligent, thinking performers, a central theme in physical education curriculum documents worldwide The traditional 'one-way-fits-all' pedagogical approach, which erroneously assumes that one movement pattern acts as an optimal template suitable for all individual learners Schöllhorn et al 2012), is also failing physical education students on a psychological level. Emphasising the mastery of specific techniques in drills and competitive games can sometimes humiliate, marginalise and exclude less gifted and confident individuals (Ennis 1999;Light and Georgakis 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional 'one-way-fits-all' pedagogical approach, which erroneously assumes that one movement pattern acts as an optimal template suitable for all individual learners Schöllhorn et al 2012), is also failing physical education students on a psychological level. Emphasising the mastery of specific techniques in drills and competitive games can sometimes humiliate, marginalise and exclude less gifted and confident individuals (Ennis 1999;Light and Georgakis 2005).…”
Section: Introductionmentioning
confidence: 99%
“…From a nonlinear pedagogy perspective, the importance of implementing practice in unstructured environments to promote informal learning opportunities is supported by the work of Schöllhorn and colleagues (2012) in sport, who demonstrated that there is sufficient evidence of the differential approach's greater benefits for learning particular movement techniques, in contrast with other approaches that are based on repetition and correction. For instance, in football, three groups, one traditionally trained with repetition and correction oriented approaches; and the other two trained with the differential approach, with blocked and random sequences of training on shooting at a goal and ball control tasks, occurring twice a week, for a period of four weeks (Schöllhorn, et al, 2012). The findings showed noteworthy benefits for both differential groups in the learning and acquisition phases in comparison with the traditional group.…”
Section: Master Teachers As Role Modelsmentioning
confidence: 94%
“…The findings showed noteworthy benefits for both differential groups in the learning and acquisition phases in comparison with the traditional group. This suggests that the differential approach is superior to the traditional approach for learning movement technique because the former perturbs individuals towards learning more functional patterns during unstructured practice; whereas the latter is more limited for learning because it follows a direct linear path, by means of implementing repetition and correction (Schöllhorn, et al, 2012). This utilization of unstructured learning environments is distinct from Hilda's engagement in highly structured activity; therefore, it might provide an alternative model to that of the pedagogic development of movement performance educators .…”
Section: Master Teachers As Role Modelsmentioning
confidence: 99%